Mechanical Behavior Analysis of Y-Type S-SRC Column in a Large-Space Vertical Hybrid Structure Using Local Fine Numerical Simulation Method - Jianguang Yue (Advances in Materials Science and Engineering)
In a large spatial structure, normally the important members are of special type and are the safety key for the global structure. In order to study the mechanical behavior details of the local member, it is difficult for the common test method to realize the complex spatial loading state of the local member. Therefore, a local-fine finite element model was proposed and a large-space vertical hybrid structure was numerically simulated. The seismic responses of the global structure and the Y-type S-SRC column were analyzed under El Centro seismic motions with the peak acceleration of 35 gal and 220 gal. The numerical model was verified with the results of the seismic shaking table test of the structure model. The failure mechanism and stiffness damage evolution of the Y-type S-SRC column were analyzed. The calculated results agreed well with the test results. It indicates that the local-fine FEM could reflect the mechanical details of the local members in a large spatial structure.